Investigation of rates of chemical reaction using laplace transform method - Ibrahim Ali , Noorbatcha (Universiti Malaya, 2001)
This paper discusses the application of Laplace Transform (LT) method in solving the rate equations for the decomposition of benzocaine, which is a first order reaction and the decomposition of acetyl phenyl salicylate (APS) which involves a competitive sequential four components reaction. The mechanisms of these reactions are already known. The results obtained using LT method can be obtained using any other methods. However we show that, for more complicated systems such as the hydrolysis of APS, LT method is more simple and straight forward compared to other methods.